Case report: Stenosis turned leak … and turned stenosis—complications of paravalvular prosthetic leak closure with a plug device - Pitta Gros, Barbara; Roux, Olivier; Eeckhout, Eric; Kirsch, Matthias (Frontiers in Cardiovascular Medicine, 2023)
Background Paravalvular leak is one of the most common complications and is among the most important prognostic factors of short- and long-term mortality after transcatheter aortic valve implantation (TAVI). Percutaneous valvular leak repair constitutes a first-line treatment for paravalvular leaks and is associated with high success rates and few serious complications nowadays. To the best of our knowledge, this is the first case where placement of the device through the stenting of the bioprosthesis resulted in creating a new symptomatic stenosis that required surgery. Case summary We present a case of a patient with low-flow, low-gradient aortic stenosis treated with transfemoral implantation of a biological aortic prosthesis. One month after the procedure, the patient presented with acute pulmonary oedema and a paravalvular leak was discovered, which was corrected by percutaneous repair with a plug device. Five weeks after the valvular leak repair, the patient was readmitted for heart failure. At this time, a new aortic stenosis and paravalvular leak were diagnosed and the patient was referred for surgery. The new aortic mixed diseased was caused by the positioning of the plug device through the valve's metal stenting, which resulted in a paravalvular leak and pressed against the valve's leaflets, causing valvular stenosis. The patient was referred for surgical replacement and evolved well afterward. Conclusion This case illustrates a rare complication of a complex procedure, and it highlights the need for multidisciplinary decisions and good cooperation between the cardiology and cardiac surgery teams to develop better criteria in the selection of the appropriate technique for managing paravalvular leaks after TAVI.